Automata Simulator: A mobile app to teach theory of computation. Issue 5 (9th July 2019) - Singh, Tuhina; Afreen, Simra; Chakraborty, Pinaki; Raj, Rashmi; Yadav, Savita; Jain, Dipika
Abstract: We developed a mobile app named Automata Simulator to simulate different types of automata and used it to teach the course on theory of computation. The students used the app to design and simulate automata during the lectures. The students also used a more sophisticated desktop application, JFLAP, to study advanced concepts related to automata theory after the lectures. An analysis of the examination results revealed that this approach helped the students to learn the concepts better and score 1% more marks. Moreover, a strong correlation between the marks obtained by the students for questions related to designing of automata and their total score was identified. In a survey conducted at the end of the semester, the students said that it was difficult to use two tools for learning the same concepts. However, they also felt that the combination of the two tools made the course more interactive and contributed positively in the process of learning.